Relationship of Edaphic Factors on the Pathogenicity of Root Rot of Bael Caused by Fusarium solani - Singh, M.; Sharma, Sushil; Kumar, Rakesh (Indian Forester, 2016)
An investigation to study the influence of edaphic factors on the pathogenicity of root rot of bael caused by Fusarium solani showed that the seedling mortality increased with the increase in inoculum levels of either of the media i.e. PDB and wheat grains. The maximum mortality (26.25% pre-emergence and 38.50% post-emergence) in case of mycelial mat was observed in soil inoculated with 4 kg soil whereas in case of wheat grain culture, maximum mortality (28.00% pre-emergence and 40.25% post-emergence) was observed in soil inoculated with 40g kg-1 soil. The disease incidence was observed more on young seedlings and there was significant decrease in disease incidence with the increase in seedling age. Mortality of seedlings were maximum (46.25%) when 5 days old seedlings transplanted in wheat grain inoculated soil, whereas 40 days old seedlings showed 22.50 per cent disease incidence. The maximum pre (40.25%) and post (38.50%) emergence seedling mortality was observed when soil was inoculated at 5 cm depth. The highest incidence of seedling mortality (37.25% pre-emergence and 28.25% post-emergence) was recorded in treatments where soil was inoculated 48 hour before sowing of Bael seeds. The seedling mortality increased with the increase in moisture content. The incidence was highest (28.25% pre-emergence and 40.25% post-emergence) when the seedlings were irrigated twice a day and was least (19.00% pre-emergence and 30.00% post-emergence) when irrigation was applied at two days gap.